Androgens in women - critical evaluation of the methods for their determination in diagnostics of endocrine disorders - Dušková, M; Kolátorová, L; Stárka, L (Physiological research, 2018)
The androgens dehydroepiandrosterone sulfate, dehydro-epiandrosterone, androstenedione and testosterone are routinely assessed in women, and circulating levels of these androgens reflect their production. These androgens are measured in most laboratories using various immuno-analytical methods. Recently, however, androgen assays have begun to be performed using gas or liquid chromatography combined with mass spectrometry. To better understand the difficulties and issues of androgen laboratory diagnostics, it is important to assess each of the methods used, how and why they were introduced into practice, and their advantages, limits, historic milestones and current status. It is also necessary to understand how reference ranges are determined and specifics arising from the physiology of individual androgens. Here we present a summary and discussion of these issues.
Keywords: Chromatography, Liquid; biologické markery; Biomarkers; dehydroepiandrosteron; Mass Spectrometry; referenční hodnoty; chromatografie kapalinová; androstendion; Androgens; Reference Values; Androstenedione; lidé; ženské pohlaví; androgeny; Humans; testosteron; Dehydroepiandrosterone; hmotnostní spektrometrie; nemoci endokrinního systému; Female; Endocrine System Diseases; Testosterone